Ácido cítrico via solo e seus efeitos na nutrição do cafeeiro - Lemos, Vinícius Teixeira (2015)
Exogenous use of low molecular weight organic acids has been very recently tested in agriculture. However, studies conducted to test the effect of these acids, especially citric acid, by means of nutritional analysis in plants and chemical attributes of soil, are of fundamental importance. The objective in this study was to evaluate productivity, chemical attributes of soil, nutritional status, and sufficiency range of nutrients in coffee (Coffea arabica), during four harvesting seasons, subjected to the application of citric acid (CA) in two regions of Minas Gerais (MG), Brazil. The experiments were conducted at private farms. One in Diamantina (MG), in Yellow Argisol dystrophic (YAd), and another in Campos Altos (MG), in Red Oxisol dystrophic (ROd). In both cultivation locations, we used Coffea arabica, cultivar Catuaí Vermelho IAC-99, with ages of four and six years, and one plant per pit in spacings of 4.0 x 0.80 m and 4.0 x 0.75, respectively. The experimental design used was of randomized blocks design, with four blocks and two replicates per block. The treatments were comprised of four doses of CA (0, 1, 2 and 4 kg ha-1 ), in single application via watering can, under the projection of the plant shoot, in December of 2008, 2009, 2010 and 2011. We evaluated the productivity of processed coffee from four harvests (from 2009 to 2012), and the chemical attributes (pH, total P, P rem, K, Ca, Mg, H+Al, CEC at pH 7, V% and C.O.) and foliar contents of micro and micronutrients, at both cultivation locations. We also determined the foliar sufficiency ranges for the mean of four coffee harvests at both locations. With the results obtained, we concluded that the coffee plant responded in grain productivity to the application of increasing doses of citric acid at both locations. The doses of CA for maximum and 90% of maximum production were of 2.9 and 0.9 kg ha-1 , with gains of up to 23.0% in YAd and, productions of 2.0 and 0.3 kg ha-1 , with gains of up to 8.5% in ROd. Small doses of CA in YAd promoted base equilibrium, did not alter pH and base saturation, and no changes organic carbon. In ROd, CA promotes the linear increase in the content of rem P and does not alter pH and base saturation. The sufficiency ranges for the coffee plant, correspondent to 90-100% of the maximum leaf production under the application of CA, were of: 0.16-0.22 dag kg-1 for P; 3.04-3.00 dag kg-1 for K; 1.32-1.26 dag kg-1 for Ca; 0.15-0.14 dag kg-1 for Mg; 0.31-0.27 dag kg-1 for S; 63.55-58.23 mg kg-1 for B (only for Diamantina); 35.01-43.97 mg kg-1 for Cu (only for Diamantina); 95.55-94.47 mg kg-1 for Fe; 81.31-86.59 mg kg-1 for Mn (only for Diamantina); 23.67-28.16 mg kg-1 for Zn.